Radiology teaching for future paediatricians. (24th May 2012) - Birahinduka, D; Kaj, B; Sinha, I; Massoud, AF
Abstract : Background: Imaging, an integral part of paediatric clinical practice, often requires a specialist opinion. Although traditionally this opinion comes from paediatric radiologists or radiologists with a special interest in paediatrics, paediatricians need to be able to interpret imaging for clinical decision-making. Paediatric radiology teaching takes place in departmental radiology meetings, where challenging cases are discussed in a multidisciplinary forum. It is however unclear how these sessions assist trainees beyond spotting diagnosis and help them in acquiring appropriate skills to assess radiology images. Aim: To formally investigate paediatric trainees' experience on radiology teaching and to establish how best they would like to gain experience in analysing radiology images. Methods: An 18-question survey was created using an online tool and distributed by email to paediatric trainees within the local deanery. Questions were designed to identify trainees' learning experience in paediatric radiology and suggestions for improvement. Results: One hundred and one paediatric junior doctors completed the survey. 93 (92%) were in paediatric training posts. 28 respondents (27.7%) were at level 1 training (ST1-3), 20 (19.8%) at level two training (ST4-5), while 44 respondents (43.5%) were at level 3 (ST6-8). Senior trainees combined with staff grade and associate specialist constituted 51.4% of the cohort. Among respondents 84 (85.28%) had a radiologist with paediatric interest in their department and held regular radiology meetings. The majority of respondents (96%) felt confident in x ray interpretation. The perception of the role of radiology meetings (figure 1 ) depended on the level of training. Senior trainees felt a need in learning how to assess MRI (figure 2 ) whereas junior trainees learning needs were across all the types of imaging (Chi-Sq = 4.148, DF = 1, p= 0.042). The most junior trainees felt their training needs in radiology images assessment would be achieved by regular departmental radiology teaching (figure 3 ), while their senior colleagues suggested radiology training courses for paediatric trainees (Chi-Sq = 3.179, DF = 1, p= 0.075). Conclusion: There is no uniform formal training system in place to prepare paediatric trainees to acquire skills required to assess competently radiology images. Both in house regular radiology teaching and radiology training courses would increase trainees' ability to assess images confidently.